2015
DOI: 10.4103/2152-7806.148547
|View full text |Cite
|
Sign up to set email alerts
|

Posterior fossa giant tumefactive perivascular spaces: 8-year follow-up in an adolescent

Abstract: Background:Cystic masses in the posterior fossa are ominous appearing lesions with broad differential diagnosis. Giant tumefactive perivascular spaces (GTPS) are rarely occurring pathological findings in the posterior fossa with unclear etiology and ill-defined long-term prognosis.Case Description:We present a case of a 15-year-old male diagnosed with posterior fossa GTPS. The patient remained asymptomatic during the 8-year follow-up after diagnosis with the serial magnetic resonance imaging (MRI) showing no c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Proton MR spectroscopy was performed to characterize giant PVSs in only a few cases in the published literature (20)(21)(22)(23). In two pediatric patients who underwent MR spectroscopy in the literature, MR spectroscopy demonstrated normal metabolite distribution without choline increase and lactate peaks in the cerebral hemispheric and cerebellar giant PVSs (20,21). On the other hand, Mascalchi et al (23) reported proton MR spectroscopy features of two mesencephalic giant PVSs.…”
Section: Discussionmentioning
confidence: 99%
“…Proton MR spectroscopy was performed to characterize giant PVSs in only a few cases in the published literature (20)(21)(22)(23). In two pediatric patients who underwent MR spectroscopy in the literature, MR spectroscopy demonstrated normal metabolite distribution without choline increase and lactate peaks in the cerebral hemispheric and cerebellar giant PVSs (20,21). On the other hand, Mascalchi et al (23) reported proton MR spectroscopy features of two mesencephalic giant PVSs.…”
Section: Discussionmentioning
confidence: 99%
“…Tumefactive VRs at other locations There were 16 patients (8 females; mean age 45.1 years; age range 6-86 years) with tumefactive VRs at other locations. These locations were the middle cerebellar peduncle and/or pons region (n = 3) [16,29,54], cerebral peduncle, pons, middle cerebellar peduncle, and dentate nucleus (n = 1) [49], dentate nucleus (n = 1) [3], anterior temporal pole (n = 9) [12,21,22,41], hippocampus (n = 1) [72], and widespread locations (left temporal and occipital lobe, bilateral basal ganglia and thalami, along subependymal lining of temporal, occipital horn and body of left lateral and fourth ventricle, left periventricular white matter, left cerebellar hemisphere and vermis) (n-1) [51].…”
Section: Literature Searchmentioning
confidence: 99%
“…In 5/ 17 (29.4%) patients, presenting symptoms were attributed to the presence of tumefactive VRs [16,17,22,29,72]. A 15-year-old male patient underwent biopsy of tumefactive VRs in the middle cerebellar peduncle; in the postoperative period, the patient completely recovered from upper gaze palsy and double vision, as well as his left hemiparesis and hemihypesthesia [16]. Follow-up MRI up to 8 years showed no change of the tumefactive VRs [16].…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations